2022
DOI: 10.3390/ijms232214185
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin Ameliorates Ovalbumin-Induced Asthma in Mice through Reducing Dendritic-Cell-Derived Th2 Cell Responses

Abstract: Asthma is a chronic respiratory disease with symptoms such as expiratory airflow narrowing and airway hyperresponsiveness (AHR). Millions of people suffer from asthma and are at risk of life-threatening conditions. Lactoferrin (LF) is a glycoprotein with multiple physiological functions, including antioxidant, anti-inflammatory, antimicrobial, and antitumoral activities. LF has been shown to function in immunoregulatory activities in ovalbumin (OVA)-induced delayed type hypersensitivity (DTH) in mice. Hence, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In vitro LF influenced T-cell differentiation in the spleen, increasing the number of regulatory T cells (Foxp3+) and decreasing Th2-associated IL-4+ T cells, which suggests a shift towards a less allergic, more regulated immune response. It also led to the reduced expression of CD80 and CD86 on dendritic cells, suggesting inhibited DC activation and a shift toward a less allergic immune response [ 144 ]. In addition to the effects of LF on the allergic inflammatory cascade, two highly similar studies assessed the impact of milk-derived hLF on inflammation induced by oxidative stress in ragweed allergen-induced allergic asthma, utilising human respiratory epithelial cells in vitro and murine models in vivo.…”
Section: Lactoferrin Clinical Application In Allergic Airway Diseasesmentioning
confidence: 99%
“…In vitro LF influenced T-cell differentiation in the spleen, increasing the number of regulatory T cells (Foxp3+) and decreasing Th2-associated IL-4+ T cells, which suggests a shift towards a less allergic, more regulated immune response. It also led to the reduced expression of CD80 and CD86 on dendritic cells, suggesting inhibited DC activation and a shift toward a less allergic immune response [ 144 ]. In addition to the effects of LF on the allergic inflammatory cascade, two highly similar studies assessed the impact of milk-derived hLF on inflammation induced by oxidative stress in ragweed allergen-induced allergic asthma, utilising human respiratory epithelial cells in vitro and murine models in vivo.…”
Section: Lactoferrin Clinical Application In Allergic Airway Diseasesmentioning
confidence: 99%
“…Given before sensitization, LF prevented inflammation, while given during it reduced the process [ 119 , 120 ]. In a similar vein, a recent study found that in an ovalbumin (OVA) mice model of asthma, oral LF during sensitization abolished airway hyperreactivity and inflammation by decreasing the elevated levels of TNF-α, IL-4, IL-5, IL-13 and increasing the downregulated levels of the anti-inflammatory IL-10 in BALF [ 121 ].…”
Section: The Role Of Lactoferrin In Lung Diseasesmentioning
confidence: 99%